Validation of Potential Reference Genes for Real-Time qPCR Analysis in Pharaoh Ant, Monomorium pharaonis (Hymenoptera: Formicidae) - Ding, Guo; Gao, Qionghua; Chen, Jun; Zhao, Jie; Zhang, Guojie; Liu, Weiwei (Frontiers in Physiology, 2022)
Ants are highly diverse social insects living in colonies consisted of up to millions of individuals with reproductive division of labors. Due to the interests in disclosing the genetic and epigenetic regulation mechanisms underlying the distinct developmental trajectories between castes and division of labor in colonies, many ant species have recently been established as laboratory models for evolutionary development and social behavior studies. These functional studies often request a precise quantification of the relative gene expression level, which relies on a stably expressed reference genes for normalization. A core set of reliable reference genes for this purpose however has not been established yet in ants. In the present study, we tested the expression patterns and amplification efficiencies of 12 abundantly expressed candidate genes in Monomorium pharaonis, one of the few ant species that are suitable for laboratory rearing and experimentation. We quantified the expression levels of these genes by RT-qPCR in seven different conditions: embryo development, sexual development, worker development, adult phenotypes, body regions, and two abiotic manipulative treatments in pharaoh ant. Finally, five genes, elongation factor-1 alpha (EF1A), glyceraldehyde 3-phosphate dehydrogenase (GAPDH), TATA-box-binding protein (TATA), tubulin gamma-2 chain-like (TBLg2), heat shock protein 67B2-like (HSP67) were found to be the most stable reference genes across seven conditions. We also identified the most stable reference genes applicable for each distinct condition and the optimal number of refence genes entailed were evaluated. Our study validates reliable reference genes for RT-qPCR analysis which lays the foundation for future studies in pharaoh ant.